Environment and Human Rights - WOLFGANG SACHS (Development, 2004, 47(1) (42-49), 2004)
Wolfgang Sachs argues for environmental human rights as a fundamental prerequisite to end the violence of development. He outlines the numerous conflicts over naturalresources in the struggle for livelihoods and argues for a transition to sustainability in the more affluent economies, in both the North and South, as a necessary condition for the safeguarding of the subsistence rights of those whose livelihood depends on direct access to nature.